Analysis of outcome of percutaneous versus open pedicle screw fixation in the treatment of thoraco-lumbar spine fractures: a prospective comparative study - Kumar, Raj; Sarkar, Bhaskar; Ifthekar, Syed; Mittal, Samarth; Kandwal, Pankaj; Azam, Quamar (International Journal of Research in Orthopaedics, 2021)
Background: Aim of the study was to evaluate the effectiveness between percutaneous and open pedicle screw fixation in the treatment of traumatic thoracolumbar burst fractures with spinal injury. Methods: A prospective comparative study including thirty patients with thoracolumbar burst fracture were equally divided into an open pedicle screw fixation (OPSF) group and a percutaneous pedicle screw fixation (PPSF) group. Demographic characteristics, clinical and radiological outcomes, and adverse events were assessed and compared between the 2 groups. Results: Demographic and clinical features including age, gender, fracture level, mechanism of injury and neurological status in both groups were not significantly different (all p>0.05). The PPSF group exhibits significantly lower operative time, intraoperative blood loss, and hospital stay compared with the OPSF group (all p<0.05). There was no significant difference in the sagittal Cobb′s angle (CA), fracture vertebral body angle (VBA), anterior vertebral body height (AVBH) on pre-operative, immediate post-operative and final follow up between the two surgical techniques (all p>0.05). Visual analogue scale (VAS) remarkably decreased in both groups after surgery but difference was not statically significant (p=0.808). Common postoperative complications in both groups were superficial infections, pressure ulcer and urinary tract infection (UTI) worsening. Hardware failure was seen only in one case of PPSF group. Conclusions: Patients with thoracolumbar burst fractures can be effectively managed with PPSF/OPSF. There were no significant differences in radiological and clinical outcomes and post-op complications between 2 groups but blood loss, operative time and hospitalization stay were less in percutaneous group, which may represent a potential benefit.